Market update: Sixty years of change in Papua New Guineaʼs fresh food marketplaces - Sharp, Timothy; Busse, M.; Bourke, R.M. (WILEY, 2022)
Open-air marketplaces are vital to food security, livelihoods, and the national economy in Papua New Guinea (PNG). Over the past 60 years, rapid growth of urban populations, changes in global commodity prices, and the decline in value of the PNG currency have stimulated demand for domestic fresh food. Selling fresh food in marketplaces has also become an attractive way to earn money for rural producers, whose returns on labour on their export crops have declined, and for urban residents struggling to make a living. This in turn has led to significant changes in PNGʼs marketplaces: spatial and temporal changes, changes in what is bought and sold, changes in who is selling, and changes in how food is transacted. In this paper, we bring together research on PNGʼs marketplaces from between 1961 and 2022 to document these changes and their causes, alongside important continuities, and to examine the implications and substantial gaps in our knowledge.